The Development of Discovery Learning Assisted Geogebra Teaching Materials on Three Dimensional to Invrease Spatial Ability of Senior High School Students - Agus Waringin; Euis Eti Rohaeti; Asep Ikin Sugandi ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2023)
The purpose of this research is to develop three-dimensional teaching materials using Geogebra-assisted discovery learning models that are valid, practical, and effective. The research method used is development using the ADDIE model, in this study it only reached the development stage, the research instrument used was material expert and media expert validation sheets as well as student response practicality sheets and ability tests in the form of tests in the form of exam questions as many as 5 questions. The research subjects for the limited test were 10 students of class 12-IPA-7. For the broad test, there were 37 students in class 12-IPS-1. Based on the results of the research that has been done, it was found that the analysis of the validation results of material experts was 4.21 with a percentage of 84.11% in the very valid category and media expert validation was 4.19 with a percentage of 83, 79% in very valid category. In the limited test, analysis of the results of the practicality sheet of 10 students obtained an average percentage of 69.17% in the practical category and in the broad test of 37 students obtained an average percentage of 83.76% in the very practical category. In the effectiveness test it was obtained that 81.05% were in the Very Good criteria. Thus, the three-dimensional teaching materials using the geogebra-assisted discovery learning model are eligible to meet valid and practical criteria for use in learning mathematics. In the effectiveness test it was obtained that 81.05% were in the Very Good criteria.